1997
DOI: 10.1093/jn/127.12.2363
|View full text |Cite
|
Sign up to set email alerts
|

Folate Status Response to Controlled Folate Intake in Pregnant Women

Abstract: A metabolic study (84-d) was conducted to investigate the folate status response of pregnant subjects (n = 12) during their second trimester and nonpregnant controls (n = 12) to folate intakes approximating the current (400 microg/d) and former (800 microg/d) recommended dietary allowance (RDA). The overall goal of the study was to provide metabolic data to assist in the interpretation of the current RDA for folate. Subjects were fed a controlled diet containing 120 +/- 15 microg/d (mean +/- SD) folate and eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…This higher demand may be explained by accelerated folate breakdown (Kownacki Brown et al 1993;McPartlin et al 1993). However, Caudill et al (1997) found no differences between pregnant and non-pregnant women with respect to increase in serum folate or erythrocyte folate concentrations or in urinary excretion of 5-methyltetrahydrofolate after supplementation with 450 and 850 g folate/d. Although the same research group suggested, from results of a controlled dietary trial, that pregnant women made more efficient use of 450 g folic acid than of 850 g folic acid, they found no significant difference in catabolism between pregnant and non-pregnant women .…”
Section: Host-related Factorsmentioning
confidence: 99%
“…This higher demand may be explained by accelerated folate breakdown (Kownacki Brown et al 1993;McPartlin et al 1993). However, Caudill et al (1997) found no differences between pregnant and non-pregnant women with respect to increase in serum folate or erythrocyte folate concentrations or in urinary excretion of 5-methyltetrahydrofolate after supplementation with 450 and 850 g folate/d. Although the same research group suggested, from results of a controlled dietary trial, that pregnant women made more efficient use of 450 g folic acid than of 850 g folic acid, they found no significant difference in catabolism between pregnant and non-pregnant women .…”
Section: Host-related Factorsmentioning
confidence: 99%
“…Serum folate may be better able to discriminate between different levels of folate intake. For instance, in a study using controlled daily intake of 450 μ g versus 850 μ g folic acid over 12 weeks, the 850 μ g group had higher serum folate concentrations but the same red cell folate levels as the 450 μ g group [ 86 ]. A meta-analysis of supplementation studies has shown a 2.13 nmol/L increase in serum folate concentration for every 0.1 mg/ day increase in folic acid intake in women 20 -25 [ 87 ].…”
Section: Response To Supplementation and Fortificationmentioning
confidence: 99%
“…Most importantly, excessive folic acid is eliminated through the urine primarily in its metabolic forms, 20 especially 5-methyltetrahydrofolate, 75 and thus results in a waste of SAM and the methyl donors. Folic acid supplementation and fortification have been found to significantly increase the urinary excretion of 5-methyltetrahydrofolate.…”
Section: Folic Acidmentioning
confidence: 99%
“…Folic acid supplementation and fortification have been found to significantly increase the urinary excretion of 5-methyltetrahydrofolate. 75 Theoretically, excessive folic acid may worsen rather than alleviate methyl-group deficiency. In fact, studies have demonstrated that folic acid supplementation neither lowers SAH, nor increases SAM, nor alters SAM/SAH ratio.…”
Section: Folic Acidmentioning
confidence: 99%